United Republic of Tanzania : Staff Report on the 2014 Article IV Consultation, the Third Review Under the Standby Credit Facilty Arrangement, Request for a Waiver for Nonobservance of a Performance Criterion, and Financing Assurances Review. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2014)
KEY ISSUES Background, outlook, and risks. Economic growth is projected to remain strong at 7 percent next year and in the medium term. Inflation is at 6 percent, gradually converging to the authorities' 5 percent medium term objective. The external current account deficit remains among the largest in the region, at 14 percent of GDP this year. Fiscal revenue shortfalls and overruns in domestically-financed spending led the deficit to rise to 6.8 percent of GDP in 2012/13. Revenue shortfalls in 2013/14 compared to the budget approved by parliament have prompted the authorities to undertake expenditure cuts during the fiscal year in an effort to meet their 5 percent of GDP target. Based on the debt sustainability analysis, Tanzania remains at low risk of debt distress. A major upside risk for the long term, not yet incorporated in the baseline projections, relates to sizable finds of offshore natural gas that, if confirmed as commercially viable, could bring in large revenues during the next decade. Program implementation. All performance criteria under the program were met, except a sizable breach of the performance criterion on net domestic financing at end-June 2013. The structural benchmark on submission to parliament of the VAT reform for November 2013 was missed. The authorities have taken corrective measures. Macroeconomic and structural policies. Preparations for the draft 2014/15 budget are under way. A VAT reform aimed at improving efficiency and reducing exemptions is ready for submission to parliament prior to the beginning of the new fiscal year. A priority in the next few years is to establish the institutional and policy framework to ensure that, if natural gas revenues materialize, they will bring benefits to all Tanzanians. Staff recommends completion of the third (and final) review under the SCF arrangement and approval of the authorities' requests for a waiver for nonobservance of a performance criterion and for completion of the financing assurances review.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet